Potential effect of Wolbachia on virus restriction in the spider mite T. truncatus - Ferreira, Lucas Yago Melo; Santos, João Pedro Nunes; Souza, David Gabriel do Nascimento; Orellana, Lixsy Celeste Bernardez; de Santana, Sabrina Ferreira; Sousa, Anderson Gonçalves; Fonseca, Paula Luize Camargos; Silva, Amanda Gabrielly Santana; Santos, Vinicius Castro; de Faria, Isaque João da Silva; Olmo, Roenick Proveti; Pacheco, Luis Gustavo Carvalho; et al. (Frontiers in Microbiology, 2025)
The mite T. truncatus is a significant agricultural pest and may serve as a potential vector for viral transmission. However, the virome of T. truncatus remains understudied. Through metatranscriptomic analyses of publicly available data, we uncovered a diverse range of viruses associated with the spider mite, including crop-infecting pathogenic species such as Potato virus Y and Cherry virus A, and fourteen previously unknown viruses across several families (e.g., Virgaviridae, Dicistroviridae, Kitaviridae, Betaflexiviridae, and Nudiviridae). Taking advantage of mite samples under different conditions, we also assessed the impact of biotic (Wolbachia and Spiroplasma infection) and abiotic stresses (pesticide exposure and temperature stress) on the T. truncatus virome. Interestingly, Wolbachia appeared to restrict viral infections in T. truncatus by reducing viral diversity and abundance, with a pronounced effect on dicistroviruses. Surprisingly, a similar effect also observed with Spiroplasma. However, the viral restriction phenotype vanishes in co-infected mites. Transcriptomics analysis of singly-infected mites revealed upregulation of piRNA and autophagy-related genes, while lipid metabolism processes-related genes were downregulated, indicating an endosymbiont-sharing mechanisms of viral interference. Although the impact of abiotic stressors on the virome was not statistically significant, Potato virus Y and TtDV-2 viruses were absent in abamectin-exposed mites, suggesting a potential reduction in the viral diversity, while heat-stressed mites exhibited slightly higher viral diversity compared to those raised at regular temperatures. Overall, our work provides a detailed analysis of the T. truncatus virome, shedding light on how endosymbionts and environmental factors shape viral dynamics and offering potential insights for pest management strategies.